Elective Lower Segment Cesarean Section in Patients with Severe Mitral Stenosis under Sole Epidural Anesthesia: Initial Experiences Case Report - Shrestha, Amit; Oli, Samana; Baral, Dilip; Parajuli, Bashu Dev (Journal of Institute of Medicine Nepal, 2022)
Management of a pregnant females with rheumatic heart disease is always challenging due to pregnancy related hemodynamic changes, which is further complicated by the pre-existing heart disease. We, here, report unique successful management of two pregnant women with multi-valvular heart disease, amongst severe mitral stenosis, who underwent elective lower segment cesarean section, under sole epidural anesthesia on contrary to general or spinal anesthesia. In woman with severe stenotic valvular heart disease especially aortic and mitral stenosis, it is always challenging to carry out the pregnancy to term, hence planned cesarean delivery at 36-37 weeks of gestation is always preferred mode of delivery for better maternal and fetal outcomes.